Addressing Common Concerns about Online Student Ratings of Instruction: A Research-Informed Approach - Winer, Laura R.; di Genova, Lina; Costopoulos, Andre; Cardoso, Kristen (Canadian Journal of Higher Education, 2017)
Concerns over the usefulness and validity of student ratings of instruction (SRI) have continued to grow with online processes. This paper presents seven common and persistent concerns identified and tested during the development and implementation of a revised SRI policy at a Canadian research-intensive university. These concerns include bias due to insufficient sample size, student academic performance, polarized student responses, disciplinary differences, class size, punishment of rigorous instructor standards, and timing of final exams. We analyzed SRI responses from two mandatory Likert scale questions related to the course and instructor, both of which were consistent over time and across all academic units at our institution. The results show that overall participation in online SRIs is representative of the student body, with academically stronger students responding at a higher rate, and the SRIs, themselves, providing evidence that may moderate worries about the concerns.